Dealloying of Al2Cu, Al7Cu2Fe, and Al2CuMg intermetallic phases to form nanoparticulate copper films. Issue 4 (14th February 2014) - Lebouil, S.; Tardelli, J.; Rocca, E.; Volovitch, P.; Ogle, K.
<x xml:space="preserve">Abstract</x> Copper rich intermetallic particles are common in technical aluminum alloys. When exposed to an aggressive electrolyte, these particles undergo a transformation into a pure copper phase due to a selective dissolution or dealloying mechanism. In this work, the kinetics of this transformation have been investigated using synthetic intermetallic phases of Al2Cu, Al7Cu2Fe, and Al2CuMg in 2 M H2SO4 as commonly used in the anodization process. The elementary dissolution rates for Al, Mg, Cu, and Fe were measured as a function of time and potential using atomic emission spectroelectrochemistry (AESEC). From this data, it was possible to measure the degree of selective dissolution for the individual elements in the different potential domains. Mg and Fe dissolve simultaneously with Al during the overall polarization. Al dissolution is activated in the presence of Mg and inhibited in the presence of Fe. This work demonstrates the utility of atomic emission spectroelectrochemistry for the direct measurement of dealloying reactions and the indirect measurement of residual films.